Factors influencing the higher incidence of tuberculosis among migrants and ethnic minorities in the UK - Hayward, S; Harding, R; McShane, H; Tanner, R (F1000, 2018)
Migrants and ethnic minorities in the UK have higher rates of tuberculosis (TB) compared with the general population. Historically, much of the disparity in incidence between UK-born and migrant populations has been attributed to differential pathogen exposure, due to migration from high-incidence regions and the transnational connections maintained with TB endemic countries of birth or ethnic origin. However, focusing solely on exposure fails to address the relatively high rates of progression to active disease observed in some populations of latently infected individuals. A range of factors that disproportionately affect migrants and ethnic minorities, including genetic susceptibility, vitamin D deficiency and co-morbidities such as diabetes mellitus and HIV, also increase vulnerability to infection with Mycobacterium tuberculosis (M.tb) or reactivation of latent infection. Furthermore, ethnic socio-economic disparities and the experience of migration itself may contribute to differences in TB incidence, as well as cultural and structural barriers to accessing healthcare. In this review, we discuss both biological and anthropological influences relating to risk of pathogen exposure, vulnerability to infection or development of active disease, and access to treatment for migrant and ethnic minorities in the UK.